2019
DOI: 10.3389/fphar.2019.00720
|View full text |Cite
|
Sign up to set email alerts
|

The Insula: A Brain Stimulation Target for the Treatment of Addiction

Abstract: Substance use disorders (SUDs) are a growing public health concern with only a limited number of approved treatments. However, even approved treatments are subject to limited efficacy with high long-term relapse rates. Current treatment approaches are typically a combination of pharmacotherapies and behavioral counselling. Growing evidence and technological advances suggest the potential of brain stimulation techniques for the treatment of SUDs. There are three main brain stimulation techniques that are outlin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(64 citation statements)
references
References 236 publications
(285 reference statements)
2
60
0
2
Order By: Relevance
“…The human insula has also become a target for treatment in a variety of disorders such as substance abuse, depression, anxiety disorders, schizophrenia, and autism. Specifically, dopamine and opioid receptors in the insular cortex are thought to influence addiction (Ibrahim et al, 2019). Our findings highlight the role of attachment in sustained romantic love and are consistent with theories suggesting that romantic love is a "natural addiction" (Fischer et al, 2016).…”
Section: Dopamine Gene Polymorphisms (Drd4 and Comt) And Romantic Love Maintenancesupporting
confidence: 87%
“…The human insula has also become a target for treatment in a variety of disorders such as substance abuse, depression, anxiety disorders, schizophrenia, and autism. Specifically, dopamine and opioid receptors in the insular cortex are thought to influence addiction (Ibrahim et al, 2019). Our findings highlight the role of attachment in sustained romantic love and are consistent with theories suggesting that romantic love is a "natural addiction" (Fischer et al, 2016).…”
Section: Dopamine Gene Polymorphisms (Drd4 and Comt) And Romantic Love Maintenancesupporting
confidence: 87%
“…The insular cortex is a part of the cerebral cortex, and connects with addiction-related areas to form a wide range of addictive brain network, and plays an important role in the three stages of substance use disorder cycle ( 23 ). Through its projections to the pre-frontal cortex, the amygdala and the ventral striatal nodes of the corticostriatal circuitry, the anterior insula influences executive functions and reward-related behavior ( 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, morphine-induced conditioned place preference (CPP) in rats were attenuated in studies using administration of muscarinic acetylcholine receptor antagonists and nitric oxide inhibitors into insula ( 21 , 22 ). Previous work has also confirmed that insula is involved in the neurocircuitry underlying all stages of substance use disorder, and clearly suggested that insula is a fundamental brain region in the maintenance and relapse to addictive drugs ( 23 ).…”
Section: Introductionmentioning
confidence: 86%
“…However, these effects are only temporary and generally do not prevent relapse. The insula has been suggested as a potential new brain stimulation target for treating addiction, including alcohol use disorder [100]. Recently, it was reported that repeated TMS treatment (5 days a week for 3 weeks) had no effect on alcohol drinking and relapse, as compared with sham treatment [86••].…”
Section: Non-invasive Neuromodulation Techniquesmentioning
confidence: 99%